2018
DOI: 10.1002/advs.201800666
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐to‐Semiconductor Transition and Electronic Dimensionality Reduction of Ca2N Electride under Pressure

Abstract: The discovery of electrides, in particular, inorganic electrides where electrons substitute anions, has inspired striking interests in the systems that exhibit unusual electronic and catalytic properties. So far, however, the experimental studies of such systems are largely restricted to ambient conditions, unable to understand their interactions between electron localizations and geometrical modifications under external stimuli, e.g., pressure. Here, pressure‐induced structural and electronic evolutions of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…This suggests that semiconducting properties may be achieved with appropriate tailoring of the concentration and/or distribution of nitrogen dopants in the system. Besides, mechanical deformation by strain or pressure has also been shown to induce metal-tosemiconductor switching in a variety of materials [55][56][57] and can thus offer a complementary means for promoting electron reorganization. This unique finding highlights exciting opportunities in the Sn-O-N ternary system and may lead to useful applications in photocatalysis and high-performance optoelectronics.…”
Section: Substitutional Doping At the O Sitementioning
confidence: 99%
“…This suggests that semiconducting properties may be achieved with appropriate tailoring of the concentration and/or distribution of nitrogen dopants in the system. Besides, mechanical deformation by strain or pressure has also been shown to induce metal-tosemiconductor switching in a variety of materials [55][56][57] and can thus offer a complementary means for promoting electron reorganization. This unique finding highlights exciting opportunities in the Sn-O-N ternary system and may lead to useful applications in photocatalysis and high-performance optoelectronics.…”
Section: Substitutional Doping At the O Sitementioning
confidence: 99%
“…14,15 Upon compression, Ca 2 N experiences a phase transition from a 2D electride to a semiconducting 0D electride with the formation of anionic electrons localized in atom-sized cavities, 16 which was later on confirmed by a subsequent experiment. 17 For decades, TiO 2 has been considered as a technically important material that is known to be an efficient photocatalyst for a wide range of applications (e.g., air and water purification, hydrogen evolution, and photoelectrochemical conversion, etc.). Other stoichiometries in Ti-O materials, especially for O-rich Ti-O materials (e.g., TiO, Ti 2 O 3 , and TiO 2 ) in different forms and types, also show the great potential as photocatalysts, together with other applications as ultrahard 18 and ultrastiff 19 materials.…”
Section: Introductionmentioning
confidence: 99%
“…Applying hydrostatic pressure to a Q2DE initially compresses the crystal in the c ‐direction, [ 130 ] but a further increase in pressure will trigger nontrivial phase transitions, as shown in Figure . [ 130–132 ] A combined computational–experimental study for AE 2 N ( AE = Ca, Sr, and Ba) showed that the low‐pressure rhombohedral phase (R3false¯m) transforms into a cubic phase (Fd3false¯m) at 2.8 GPa. [ 132 ] The transformation causes the ILB to disappear, forcing the excess electrons out of the interlayer space to channel‐like voids.…”
Section: Miscellaneous Properties Of 2d Electrides and Electrenesmentioning
confidence: 99%
“…[ 130–132 ] A combined computational–experimental study for AE 2 N ( AE = Ca, Sr, and Ba) showed that the low‐pressure rhombohedral phase (R3false¯m) transforms into a cubic phase (Fd3false¯m) at 2.8 GPa. [ 132 ] The transformation causes the ILB to disappear, forcing the excess electrons out of the interlayer space to channel‐like voids. The resulting material is a quasi‐1D electride with a semimetallic band structure.…”
Section: Miscellaneous Properties Of 2d Electrides and Electrenesmentioning
confidence: 99%